Peruvian health professionals' leadership styles - Franklin Jhony Julián Méndez; Cecilia Elizabeth Reyes Alfaro; Ericson Felix Castillo Saavedra; Verónica Yamilet Coronel Vega; Sara Isabel Cabanillas Ñaño; Rosa María Salas Sánchez; Julissa Estmilsinia Vargas Vigo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
Foundation: leadership represents an important trait that must be presented by every person in charge of directing a group of people. The organizational changes generated in pharmaceutical offices must be assumed through a leadership style that allows achieving the objectives and goals set, in order to ensure and optimize health care. Objective: to determine the Chemist-Pharmaceutical professionals' leadership styles who work in public and private establishments in the city of Trujillo (Peru). Methods: a descriptive cross-sectional study that included 94 collegiate professionals who work as technical directors. In data collection, the survey was used as a technique and the Multifactor Leadership Questionnaire (MLQ) as an instrument, which consisted of 36 questions on a Likert scale, distributed in three dimensions: transformational, transactional, and corrective/avoidant leadership. Results: 82.9 % of the professionals work as technical directors in the private sector; 57.4 % are female and more than 60 % have a high level of leadership. Together both sectors, the high-level transformational and transactional leadership styles were present in 28.7 % and 61.7 %, respectively; mid-level corrective/passive/avoidant leadership was present in 72.3 % of the professionals. Likewise, high-level transformational leadership was present in 62.5 % of those who work in the public sector and in 56.4 % of those in the private sector; the corrective/passive/avoidant leadership style at a medium level was present in more than 60 % of the professionals in both sectors. Conclusions: the most predominant leadership style was transactional.